The Intellectuals and the Masses / Pride and Prejudice among the Literary Intelligentsia, 1880-1939 - Carey John (Faber And Faber, 1992)
Preface, Themes, The Revolt of the Masses, Rewriting the Masses, The Suburbs and the Clerks, Natural Aristocrats, Case Studies, George Gissing and the Ineducable Masses, H. G. Wells Against H. G. Wells, H. G. Wells Getting Rid of People, Narrowing the Abyss: Arnold Bennett Wyndham Lewis and Hitler, Wyndam Lewis and the Feminization of the West Adolf Hitler's Intellectual Programme, Postcript, Notes, Index.